The Role of Social Distance between Teachers and Students in English Proficiency at MTsN Model Sumber Bungur Pakong - Mohammad Amiruddin (Penerbit STKIP PGRI Bangkalan, 2018)
A teacher undergoes fundamental changes in English language teaching. He/she creates conditions and develops activities in order that students are able to practice the language in a meaningful context. The teacher is also instrumental in creating a positive and helpful learning environment within the class. Students who feel safe and secure are much more willing to practice the target language. Meaningful classroom atmosphere promotes risk-taking and allows the students to experiment. This study aims to investigate the role of social distance between teachers and students in English language proficiency at MTsN Model Sumber Bungur Pakong. The research population comprised all the students at MTsN Model Sumber Bungur Pakong. A sample was established using the proportional stratified random sampling technique. This study is an ex post facto research, using quantitative approach. The data were analyzed by simple regression technique. The result of the study shows that the role of social distance in English proficiency level of students at MTsN Sumber Bungur Pakong is not high, 0.186 (18.6%). Social distance between teachers and students builds the students at MTsN Model Sumber Bungur Pakong inEnglish proficiency level. Students at MTsN Model Sumber Bungur Pakong have greater interaction to their teachers get more English proficiency than those who do not interaction to their teachers.